Biomass activated carbon from oil palm shell as potential material to control filtration loss in water-based drilling fluid - Umar, M. (Springer Singapore, 2020)
Activated carbon (AC) is a material that has powerful adsorptive properties. It have surface area excess 1000 m2/g and porous structure. The properties of AC can be potential material to adsorb liquid and gas phase. This study is to investigate activated carbon from palm oil shell as a solution filtration loss in water based drilling fluid. Three general processes to produce activated carbon are (1) dehydration of water by heated in oven for 1 h at 100 °C, (2) Carbonization by heated in oven for 1 h at 300 °C, and (3) Activation by heated in furnace for 1 h at 1000 °C. Scanning Electron Microscope (SEM) was used to determine the surface morphology of the activated carbon products and to find out the carbon was active. Sample of water-based drilling fluid was prepared. Standard API filtration test were carried out to discover the effect of oil palm shell activated carbon on filtration loss drilling mud. The results shows that filtration loss decrease from 21.3 ml with non activated carbon to 15 ml with activated carbon. SEM shows that activated carbon has good pores and has good adsorption properties. This result indicate that activated carbon is a potential material to control filtration loss in the water-based drilling fluid. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2020.